2021
DOI: 10.1038/s41598-021-83356-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of coronary artery spasm by ergonovine provocation test of radial artery

Abstract: We investigated the sensitivity, specificity and safety of ergonovine provocation test of radial artery in the diagnosis of coronary artery spasm (CAS). The patients who came to our hospital for chest pain from January to June 2020 as well as had coronary stenosis < 50% and no radial artery stenosis, were enrolled in this study. These patients were divided into CAS group and control group after intracoronary ergonovine provocation test. All patients underwent ergonovine provocation test of radial artery, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…At present, the preferred non-invasive diagnosis method of CAS in clinical practice is duplex ultrasound imaging, which is simple and safe, but it is easily affected by the level of operators, and it is expensive and not suitable for large-scale screening of the population. 5 The search for new, noninvasive, and less costly methods for the screening diagnosis of asymptomatic CAS is still expected to be developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the preferred non-invasive diagnosis method of CAS in clinical practice is duplex ultrasound imaging, which is simple and safe, but it is easily affected by the level of operators, and it is expensive and not suitable for large-scale screening of the population. 5 The search for new, noninvasive, and less costly methods for the screening diagnosis of asymptomatic CAS is still expected to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, current imaging has different deficiencies in the diagnosis of moderate stenosis (>50%) or severe stenosis (>70%) in asymptomatic CAS patients. For example, the preferred noninvasive diagnosis method of CAS in clinical practice is duplex ultrasound imaging, which is simple and safe, but it is easily affected by the level of operators, and it is expensive and not suitable for large-scale screening of the population [5][6][7] Therefore, the current priority is to identify and treat asymptomatic CAS patients as early as possible through noninvasive and low-cost methods to reduce the risk of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Sueda et al reported no RAS during the SPT performed by radial artery puncture [ 18 ]. However, studies reported that RAS is more likely to occur when NTG administration cannot be used immediately after radial artery puncture [ 19 ], and other studies reported an association between RAS and coronary spasm [ 20 ]. The possibility of RAS should be considered when conducting an SPT via radial artery puncture, as in this case.…”
Section: Discussionmentioning
confidence: 99%